Development of a theoretical guide for nursing care in cardiac arrest - Aliandra Bittencourt da Silva; Regimar Carla Machado (Rev Rene)
This study aimed to identify the knowledge on cardiorespiratory arrest among nurses in a hospital of Vale do Paraíba, São Paulo, Brazil, and develop a theoretical guide for care of this emergency. We prepared an instrument of data collection based on relevant literature and the 2010 AHA Guidelines for CPR, from August to October 2012. The sample consisted of 41 nurses who deliver care activities in various units of the hospital. The study showed that professional participants said they were able to act in cardiopulmonary resuscitation, however, there were limitations of knowledge about the theme. Given the above, we developed a theoretical guide for cardiac arrest care based on scientific literature and covering questions submitted by nurses.